Binder/Collector‐Free Te Cathodes: Elastic Carbon Nanotube Aerogel Meets Tellurium Nanowires: A Binder‐ and Collector‐Free Electrode for Li‐Te Batteries (Adv. Funct. Mater. 21/2016). (6th June 2016) - Xu, Jie; Xin, Sen; Liu, Jian‐Wei; Wang, Jin‐Long; Lei, Yong; Yu, Shu‐Hong
Abstract : On page 3580, J.‐W. Liu, S.‐H. Yu, and co‐workers construct two different types of two types of binder/collector‐free Te cathodes using a bifunctional and elastic carbon nanotube (CNT) aerogel and Te nanowires. Both cathodes have high specific capacity, fine cycling stability, and high‐rate capability, showing excellent promise for high‐energy rechargeable Li–Te batteries.